Physiological and molecular characteristics associated with the anti-senescence in Camellia oleifera Abel. - Z. ZHANG; Y.M. XU; Z.L. HE; C.X. LIU; R. WANG; X.N. WANG; Y.H. PENG; L.S. CHEN; S.F. PENG; L. MA; Z.G. LI; W. TANG; et al. (Photosynthetica, 2024)
This study analyzed physiological and molecular characteristics associated with the resistance to aging or anti-senescence in Camellia oleifera Abel. Trees over 100 years old (ancient trees) were compared with those about 30 years old (mature trees). Total chlorophylls, chlorophyll a/b ratio, and hydrogen peroxide concentrations in ancient tree leaves were significantly higher than in their counterparts. Significantly higher activities of superoxide dismutase, peroxidase, and catalase were detected in ancient tree leaves. Nine Chl a/b-binding protein genes, 15 antioxidant enzyme genes, 21 hormone-related genes, and 301 stress-related genes were upregulated, and 42 protein-degradation genes were downregulated in ancient tree leaves. By increasing chlorophyll content and antioxidant enzyme activities and regulating the ageing-related genes expression, ancient C. oleifera leaves maintained remarkable vitality. Although further research is needed, our study may shed some light on how ancient C. oleifera trees can resist ageing and sustain their healthy growth.